Visual Exploration of 3D Geospatial Networks in a Virtual Reality Environment. (11th December 2017) - Zhang, Meng-Jia; Zhang, Kang; Li, Jie; Li, Yi-Na
Abstract: Classic geospatial network visualization tends to limit itself to 2D representation by organizing edges and nodes on a 2D map or the external surface of a traditional 3D globe model. Visual clutters and occlusions due to edge crossings and node-edge overlaps make efficient and effective exploration of geospatial networks a challenge. This paper proposes an interactive visualization approach for the intuitive exploration of geospatial networks inside a spherical virtual reality environment. To reduce visual clutter and reveal network patterns, we also propose a parameterized 5-step 3D edge-bundling algorithm and a set of techniques to avoid collision of network edges with the viewpoint. Our spherical interaction and 3D edge-bundling approach have been implemented in an Oculus Rift VR system. We demonstrate the usefulness of our approach with two case studies on real-world network data and usability experiments.